The barrier function of an insulator couples high histone acetylation levels with specific protection of promoter DNA from methylation - Mutskov, Vesco J. (Cold Spring Harbor Laboratory Press, 2002)
Stably integrated transgenes flanked by the chicken β-globin HS4 insulator are protected against chromosomal position effects and gradual extinction of expression during long-term propagation in culture. To investigate the mechanism of action of this insulator, we used bisulfite genomic sequencing to examine the methylation of individual CpG sites within insulated transgenes, and compared this with patterns of histone acetylation. Surprisingly, although the histones of the entire insulated transgene are highly acetylated, only a specific region in the promoter, containing binding sites for erythroid-specific transcription factors, is highly protected from DNA methylation. This critical region is methylated in noninsulated and inactive lines. MBD3 and Mi-2, subunits of the Mi-2/NuRD repressor complex, are bound in vivo to these silenced noninsulated transgenes. In contrast, insulated cell lines do not show any enrichment of Mi-2/NuRD proteins very late in culture. In addition to the high levels of histone acetylation observed across the entire insulated transgene, significant peaks of H3 acetylation are present over the HS4 insulator elements. Targeted histone acetylation by the chicken β-globin insulator occurs independently of gene transcription and does not require the presence of a functional enhancer. We suggest that this acetylation is in turn responsible for the maintenance of a region of unmethylated DNA over the promoter. Whereas DNA methylation often leads to histone deacetylation, here acetylation appears to prevent methylation.